Dielectric Hole Collector toward Boosting Charge Transfer of CsPbBr3 Hybrid Nanogenerator by Coupling Triboelectric and Photovoltaic Effects. (30th May 2021) - Guo, Qiyao; Yang, Xiya; Wang, Yudi; Xu, Wenkai; Duan, Jialong; Tang, Qunwei
Abstract: Coupled triboelectric‐photovoltaic effect by collecting photogenerated charge carriers is increasingly important to dramatically improve the short‐circuit current output of triboelectric nanogenerators (TENG), especially for the all‐inorganic cesium lead bromide (CsPbBr3 ) halide perovskite combined with the optoelectronic and dielectric properties as a fundamental friction layer in TENG. Herein, hole‐extraction polydimethylsiloxane (PDMS)‐multi‐wall carbon nanotubes (MWCNTs) composite film (PC) is applied into the fabrication of vertical contact‐separation mode CsPbBr3 /PC hybrid TENG with dual role of negative triboelectrification layer and photogenerated hole collector. Through precisely regulating the surface potential of PC films by tuning the MWCNT loadings, the charge quantity is greatly enhanced thanks to the triboelectric‐photovoltaic coupling effect. The best hybrid TENG at MWCNTs loading of 16 wt% achieves a transferred charge of 0.358 mC under illumination, which is nearly 30, 000 times higher than that of the pristine PDMS based TENG. Impressively, the champion hybrid TENG at MWCNTs loading of 12 wt% yields a power rating density of 8.24 W m −2 . This work demonstrates the PC hole collector to be a promising conductive triboelectric counterpart for efficient charge separation and extraction toward booting current density of hybrid triboelectric‐photovoltaic devices. Abstract : Novel multi‐walled carbon nanotubes modulated polydimethylsiloxane composite films with tunable dielectric properties and work function are introduced as a hybrid conductive friction layer as well as an eﬃcient photogenerated hole‐extracted interface to greatly enhance the charge quantity achieved by triboelectric‐photovoltaic coupling effects.